INDIVIDUAL VARIATION OF TOXICITY IN THREE VIETNAMESE TOXIC MARINE PUFFER SPECIES - Ha, Dao Viet; SATO, SHIGERU (Vietnam Journal of Marine Science and Technology, 2012)
In Vietnam, several poisonings due to consumption of marine puffers have been reported every year for a long time, even recently.  In most cases, the causative species were those commonly found in Vietnam were Torquigener gloerfelti, Takifugu oblongtus and Lagocephalus sceleratus.  In this study, the toxicity of various organs (skin, muscle, intestine, liver and gonad) was analyzed by High Performance Liquid Chromatography (HPLC) in several specimens of above-mentioned three species which were collected from the Khanh Hoa coastal waters in 2007 and 2008.  High variation was observed in the toxicity of the organs of each species.  The gonad and the liver showed the highest toxicity, in terms of high average toxicity as well as large toxicity range: the toxicity of the gonad of T. gloerfelti was 123.2 ± 240.6 MU/g; that of the liver of T. oblongtus was 171 ± 239.3 MU/g (n=30). Especially, the muscle of L. sceleratus often showed quite high toxicity (58.7 ± 62.3 MU/g, n=12) which is dangerous for human consumption.   83% of the specimens of this species showed the toxicity higher than safety consumption level suggested in Japan (10 MU/g). These results show that these puffer species are inappropriate for food because of high level of toxin, though some nontoxic or weakly toxic specimens are included.